A Study On Association Rule Mining (International Journal of Engineering and Computer Science, 2015)
Now a days, Association Rule Mining become a major Role in Data mining. It attracts more attention because of its wide applicability. Association Mining aims to extract interesting correlations, frequent patterns, associations or casual structure among sets of items. This paper aims at giving a theoretical study on some of the existing algorithms. The concepts behind association rules are provided at the beginning followed by an overview to some of the previous research works done on this area. The merits and demerits are discussed and concluded with inference.